1986
DOI: 10.1139/v86-053
|View full text |Cite
|
Sign up to set email alerts
|

Free-radical redox reactions of uranium ions in sulphuric acid solutions

Abstract: A. JOHN ELLIOT, SHAHSULTAN PADAMSHI, and JANA PIKA. Can. J. Chem. 64, 314 (1986).The radiolytic reductio? of uranyl ions in degassed sulphuric acid solutions containing various organic solutes was studied. It was shown that while COOH, C02-, and a-hydroxy-alkyl radicals reduced uranyl ions, the P-hydroxy-alkyl radicals and those derived from gluconic acid could not affect the reduction. The oxidation of uranium(1V) by hydrogen peroxide at pH 0.7 involves hydroxyl radicals in a chain mechanism but at pH 2.0 the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…In addition, the U(IV) peak centered at 850 nm was certainly higher, while the peak at 650 nm seemed to be more defined. A very similar change of the U(IV) spectra during U(VI) radiolytic studies was found by Elliot et al, who also ascribed this change to U(III) [36]. Although U(III) is unstable, its half-life has been reported to be at least 755 h under similar conditions to ours [37], enough to be spectroscopically detected.…”
Section: Heterogeneous Photocatalytic Experimentssupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, the U(IV) peak centered at 850 nm was certainly higher, while the peak at 650 nm seemed to be more defined. A very similar change of the U(IV) spectra during U(VI) radiolytic studies was found by Elliot et al, who also ascribed this change to U(III) [36]. Although U(III) is unstable, its half-life has been reported to be at least 755 h under similar conditions to ours [37], enough to be spectroscopically detected.…”
Section: Heterogeneous Photocatalytic Experimentssupporting
confidence: 76%
“…Similarly to other electron donors, HCOOH 1) accelerates uranyl reduction by reducing the recombination rate of e CB − /h VB + pairs, and 2) is able to indirectly reduce U(VI) by • COO − [36]. Photochemical experiments at acid pH (< 2) with TiO 2 nanoparticles in the presence of high HCOOH concentrations (Fig.…”
Section: Hcooh/hcoo − + H Vbmentioning
confidence: 99%
“…• COH, a strong reducing radical [57] (E 0 ranges from −1.8 to −1.39 V [62]), which can reduce UO 2 2+ to UO 2 + , U(IV) and even to U(III) [41,63] (see however below).…”
Section: Discussionmentioning
confidence: 99%
“…(1b)), which are highly reactive for uranyl reduction to U(V) (Eq. (1c)) followed by disproportionation into U(VI) and U(IV) species [80] (Eq. (1d)).…”
Section: Tablementioning
confidence: 99%